2009
DOI: 10.1108/17515630910956561
|View full text |Cite
|
Sign up to set email alerts
|

Do interactions within networks lead to knowledge management?

Abstract: PurposeThrough Social Capital, this paper seeks to introduce interactions as antecedents of Knowledge Management.Design/methodology/approachThe paper briefly reviews the Social Capital and Knowledge Management literature. It investigates how SC impacts the KM cycle in the literature and then presents statistical evidence using a case study.FindingsSocial Capital can be considered as an appropriate infrastructure for Knowledge Management implementation.Research limitations/implicationsSocial Capital refers to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(106 reference statements)
0
4
0
1
Order By: Relevance
“…Team/organizational performance also increases (Yang et al , 2011). Monnavarian and Amini (2009) considered social capital as an appropriate infrastructure for KM implementation.…”
Section: Analysis Discussion and Conclusionmentioning
confidence: 99%
“…Team/organizational performance also increases (Yang et al , 2011). Monnavarian and Amini (2009) considered social capital as an appropriate infrastructure for KM implementation.…”
Section: Analysis Discussion and Conclusionmentioning
confidence: 99%
“…Content validity (or face validity) accesses whether the items in the scale are comprehensive and representative of the constructs (Monnavarian & Amini, 2009). The survey items in the current study were identified after an extensive review of the literature.…”
Section: Content Validitymentioning
confidence: 99%
“…Tsai & Ghoshal (1998) suggested that social capital encapsulates social interactions such as relationships, trust, and norms that support actions in a particular setting. Various conceptual and empirical studies have discussed how social capital relates to as diverse variables as the following;  Intellectual capital formation (Nahapiet & Ghoshal, 1998)  Knowledge creation (Krause, et al, 2007) and sharing (Chow & Chan, 2008;Monnavarian & Amini, 2009;Wasko & Faraj, 2005;Weber & Weber, 2007) …”
Section: Introductionmentioning
confidence: 99%
“…Competing companies based on knowledge are faced with a dilemma because organizational assets are held in the minds of individuals (Chen et al, 2009a). Knowledge assets are based on the experience and expertise of individuals working in the company so the company must provide the right structure to form knowledge into competence (Monavvarian & Amini, 2009). Therefore financial institutions should recognize the importance of systematic knowledge management (Chatzoglou & Vraimaki, 2009).. Risks managed by a financial services company based on portfolio data owned.…”
Section: Introductionmentioning
confidence: 99%